Low protein diet supplemented with ketoacids on muscle wasting in chronic kidney disease: A clinical trial - Zhang, Yueyue; Gu, Lijie; Wang, Ling; Rong, Shu; Yuan, Weijie (Frontiers in Medicine, 2022)
Aim Nutrition is an important part of the care of patients with chronic kidney disease (CKD). However, there is limited clinical research on the skeletal muscle nutrition of patients with CKD. We carried out this study to find out whether a low-protein diet supplemented with ketoacids (LPD + KA) could improve muscle wasting in patients with CKD. Methods Patients were enrolled in this non-blind, parallel-group, randomized trial assessing the nutritional status of CKD, randomly assigned to either the LPD + KA group or conventional LPD group. Blood samples such as Hemoglobin, Cystatin C, Creatinine, BUN, Albumin, Pre- Albumin, Glycerin Trilaurate, and Cholesterol were measured at baseline and every 3 months. The parameters of skeletal muscle and other body composition were assessed before and after dietary intervention for 12 months. Results A total of 58 patients with CKD completed the study and were available for further analysis. The hemoglobin and albumin were observed to be markedly improved in the LPD + KA group during the follow-up as compared to baseline. Body mass index and total body water index of both groups were increased upon follow-up but the increase in the LPD + KA group was comparatively higher. Moreover, an increase in body fat%, skeletal muscle mass index, and appendicular skeletal muscle mass index was observed in both groups between baseline and follow-up, but it was statistically insignificant. Conclusion This study did not find a significant improvement of KAs on muscle wasting, and a long time or more indices study may need to find the effects of the LPD + KA diets. Clinical trial registration [www.ClinicalTrials.gov], identifier [NCT02568020].